Kompetisi Surat Kabar Lokal Berdasarkan Tingkat Kepuasan Biro Iklan pada Layanan Jasa Media Surat Kabar - Andi Prasetiya, L. Juni (Jurnal ILMU KOMUNIKASI, 2012)
Abstract: Business newspaper has eliciting competition over source life of supporting media industry, i.e. capital, types of content and types of audience. This research explains the newspaper’s competition based on advertiser satisfaction as a benchmark of media effectiveness. Adopting the theory of uses & gratification and using variables of gratification sought and gratification obtained, these studies examine 5 local newspapers in Yogyakarta. The instrument of competitive strategy is using for further analysis, consisting of superiority direction and superiority magnitude measurements. The results showed that advertising agencies haven’t felt the satisfaction of the services provided by the local newspaper. Key words: competition, gratification sought, gratification obtained, superiority direction, superiority magnitude .Abstrak: Bisnis surat kabar telah memunculkan kompetisi yang memperebutkan sumber penunjang hidup industri media, yakni modal, isi media, dan jenis audiens. Penelitian ini menjelaskan kompetisi tersebut berdasarkan kepuasan pengiklan sebagai tolok ukur efektivitas media. Mengadopsi teori uses & gratification dengan menggunakan variabel gratification sought dan gratification obtained, penelitian ini menguji lima surat kabar lokal di Yogyakara. Selanjutnya dianalisis dengan menggunakan instrumen competitive superiority, terdiri dari superiority direction dan superiority magnitude. Hasil penelitian menunjukkan bahwa biro iklan belum merasakan kepuasan dari layanan yang diberikan oleh jasa surat kabar lokal.